1999
DOI: 10.1097/00000539-199902000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Intranasal Surgery

Abstract: We compared airway management for intranasal surgery anesthesia using a new device, the flexible reinforced laryngeal mask airway, with the current standard of tracheal intubation. The study demonstrates that the flexible reinforced laryngeal mask airway can provide a safe, protected airway with a smoother emergence from anesthesia than tracheal intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…A lower incidence of some postoperative airway complications has been reported when using the FLMA. In addition, the FLMA has been found to have some shortcomings, such as difficulty of insertion, the possibility of dislocation during the procedure, the risk of ventilation into the esophagus and stomach, and an increased risk of aspiration and partial upper airway obstruction [ 6 , 7 ]. However, many of these studies included small numbers of subjects, and their conclusions with regard to some issues are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…A lower incidence of some postoperative airway complications has been reported when using the FLMA. In addition, the FLMA has been found to have some shortcomings, such as difficulty of insertion, the possibility of dislocation during the procedure, the risk of ventilation into the esophagus and stomach, and an increased risk of aspiration and partial upper airway obstruction [ 6 , 7 ]. However, many of these studies included small numbers of subjects, and their conclusions with regard to some issues are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on LMA and ETI during adenotonsillectomy and other surgical procedures reported a significant increase in the rate of laryngospasm with ETI compared with LMA 14 - 17 whereas some others failed to show any significant increase in the rate of laryngospasm with ETI. 11 We believe that the incidence of complications associated with LMA use, include breath holding, laryngospasm, bronchospasm, increased air leakage, desaturation and ETI requirement, increase when adequate anesthesia depth cannot be achieved by volatile anesthetics due to air leaks secondary to the incomplete placement of the LMA.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the removal of airway devices was implemented when patients opened their eyes and responded to verbal commands. However, awake extubation is consequentially accompanied by excessive bleeding and oxyhemoglobin desaturation [8]. When compared to the ETT, the LMA does not directly stimulate the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…The laryngeal mask airway (LMA) has been proved to be suitable for the intranasal surgery [811]. When compared with the tracheal intubation, the LMA has many advantages, such as minimal cardiovascular response, lack of tracheal stimulation, less sore throats [12].…”
Section: Introductionmentioning
confidence: 99%